A five-year strategic plan for GT Cosmetics Manufacturing Inc. - Danao, Terrence Rigor V., Fortin, Efril F., Garcia, Jersey Red V., Geronimo, Rochelle D., Martinez, Alayne B., Moraña, Mikaela Mikee P., Peregrino, Graciella Arvi M., Santos Jr., Ricardo Rosendo S., Saplala, Stephanie H., Tamayo, Bianca Therese E., Ventenilla, Charles Andrie H. 4 0 16; 5
EXECUTIVE SUMMARY In 1994, GT Cosmetics Manufacturing Inc., a family corporation focusing on manufacturing and distributing cosmetic products, was established in Cebu. The owners, Mr. Rogelio Salvane Sr. and Engr. Leonora Salvane, started their production humbly from a part of their home and with a capital of P500.00. GT, standing for God's Talent, offers their products and services nationwide. The entity's mission is to be the greatest in everything they do by providing innovative cosmetic products and services that are of superior quality and value, bringing out the best in everyone they touch. After analyzing the five-year financial position of the firm through the use of financial ratios, the proponents have discovered that the company is facing a problem in profitability. The firm is, particularly, having issues pertaining to the following: (1) low to negative equity resulting in net loss; (2) capital deficiency; (3) incurring more costs that profit; and (4) lack of proper asset utilization. The financial ratios allowed the proponents to review the vital areas and operations of the company. Moreover, giving them a strong insight of the company's performance. To solve the problems mentioned above, the researchers have chosen the implementation of the alternative course of action of offering a new product line for toddlers. Backed by the projected cash budget, the proponents arrived at the chosen decision to achieve the desired financial objectives. This action will resolve the company's problem in profitability by increasing the sales, improving the net profit margin, increasing the return on assets, and as well as their receivables. The projected financial statements show that the chosen action will positively affect their financial operation and help the company gain more income.
Financial Management: (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2021
Keywords: 2 -- 0; 6; 20; 20; 2